Tuning Electrical Conductivity and Ultrafast Optical Nonlinearity of Reduced-GO Films Ablated by Femtosecond Laser Direct Writing - Youliang Tao; Xuefeng Zhang; Han Wang; Zhongquan Nie; Deng Pan (Molecules)
Carbon-based nanomaterials with excellent electrical and optical properties are highly sought after for a plethora of hybrid applications, ranging from advanced sustainable energy storage devices to opto-electronic components. In this contribution, we examine in detail the dependence of electrical conductivity and the ultrafast optical nonlinearity of graphene oxide (GO) films on their degrees of reduction, as well as the link between the two properties. The GO films were first synthesized through the vacuum filtration method and then reduced partially and controllably by way of femtosecond laser direct writing with varying power doses. Subsequently, the four-point probe measurements of the reduced-GO (r-GO) films were demonstrated to exhibit superior resistivity and electrical conductivity compared with the pristine-GO counterpart. It was found that the conductivity of the film increases and then decreases with increasing ablation laser power (P), and GO was completely reduced at P = 100 mW, with a resistivity and electrical conductivity of 1.09 × 10−3 Ω·m and 9.19 × 102 S/m, respectively. GO was over-reduced at P = 120 mW, with its resistivity and electrical conductivity being 3.72 × 10−3 Ω·m and 2.69 × 102 S/m, respectively. We further tested the ultrafast optical nonlinearity (ONL) of the as-prepared pristine and reduced GO with the femtosecond Z-scan technique. The results show that the behavior of ONL is reversed whenever GO is reduced in a controlled manner. More interestingly, the higher the ablation laser power is, the stronger the optical nonlinearity of r-GO is. In particular, the nonlinear absorption and refraction coefficients of the r-GO films reach up to 3.26 × 10−8 m/W and −1.12 × 10−13 m2/W when P = 120 mW. The nonlinear absorption and refraction coefficients reach 1.9 × 10−8 m/W and −3 × 10−13 m2/W, respectively, for P = 70 mW. GO/r-GO thin films with tunable photovoltaic response properties have potential for a wide range of applications in microelectronic circuits, energy, and environmental sustainability.